GROUND TEMPERATURE AT THE HENRYK ARCTOWSKI STATION (KING GEORGE ISLAND, ANTARCTIC) – CASE STUDY FROM THE PERIOD JANUARY 2012 TO FEBRUARY 2013 - ARAŹNY, ANDRZEJ; KEJNA, MAREK; SOBOTA, IRENEUSZ (Bulletin of Geography. Physical Geography Series, 2013)
The article presents the results of measurements of ground temperature in the context of general meteorological conditions at the Henryk Arctowski Station (King George Island, South Shetland Islands, Antarctic) from the period of 20 January 2013 to 22 February 2013. The measurements were taken using a Vantage Pro+ automatic weather station and the thermal conditions of the ground were measured by means of a HOBO automatic data logger. The variability of ground temperature was analysed in an annual and diurnal cycle. A clear recurrent diurnal pattern was observed in the summer season, resulting from more favourable insolation conditions in that part of the year. In the winter, on the other hand, no major differences in the diurnal cycle of ground temperature were found, particularly with a dense snow cover.